Solar battery / Muhamad Fauzi Othman … [et al.] - Othman, Muhamad Fauzi; Abdul Rashid, Mohd Fazli; Awg. Noh, Mohd lukman; Salleh, Mohd Zulkifli (2002)
It is a fact, that in future we should need an alternative way in generating power for human used to replace the unrenewable energy. It is due to the finding discovered out by the world researchers about the future of the unrenewable energy that can last about 50 to 100 years more. That is why we take an initiative to leam about this renewable energy for a future used in our country. It is totally advance for our country as it is located near the equator line, which deserved highest emission of solar regulation. From the facts, it is a waste if we do not use this advantage wisely to generate our country alternative energy supply. Therefore, in this thesis the main point is that we want to study and learn about generating the electricity power using the solar energy and store the power in the battery. As we are taking the Diploma Mechanical in Automotive and to relate to our course in this thesis we only focusing upon the lead acid battery, which is often used in the automobile. Perhaps this study, we lead in creating a new creation to assist the changing process of the battery incase of sudden malfunction of the alternator, hopefully. Other than that, we are primarily concerned in the collection and storage of solar energy to make a comparison between solar charging and electric charging, and also to determine what the main effect and efficiency of solar charging. This book of thesis consists of the chapter overall.